Perilaku Memilih Masyarakat Tionghoa dalam Pemilihan Presiden Tahun 2024 di Kelurahan Sei Rengas I - Siburian, Yeremia Elkana Tua; Pakpahan, Rugun Elis Deoktavia; Sinaga, Eko Pranata; Halking, Halking (Universitas Methodist Indonesia, 2024)
This study analyzes the voting behavior of Chinese people in the 2024 Presidential Election in Sei Rengas I Village. The main focus is to understand the socio-political dynamics of minority ethnic groups in the context of Indonesian democracy, especially related to political participation and the influence of cultural values in political decision-making. Using qualitative descriptive methods, data were collected through in-depth interviews and documentation studies of the local Chinese community. Based on the theory of voting behavior that includes sociological, psychological, and rational approaches, the results of the study show the dominance of a combination of sociological and rational approaches. Sociologically, voting behavior is strongly influenced by family and community factors. In the rational approach, economic factors are the main consideration, where voters make rational calculations regarding the candidate's ability to overcome economic challenges. Chinese voters show a tendency to be increasingly intelligent and selective in determining their choice of president, considering the economic programs offered. The study also reveals an increase in political awareness among the Chinese community which encourages more active participation in the democratic process, potentially creating a more inclusive political environment and contributing to the country's economic stability.